IGFI and IGFBP3 in diabetic pregnancy. (16th November 2010) - Higgins, M; Russell, N; Crossey, P; Nyhan, K; Brazil, D; McAuliffe, F
Abstract : The aim of this study was to investigate the action of insulin like growth factor I (IGFI) and its binding protein (IGFBP3) in non-diabetic (ND) compared to Type 1 Diabetic (T1DM) pregnancies. ND (n=25) T1DM (n=25) p Value Maternal IGFI 3.27 (0.74–11.17) 2.26 (0.3–8.18) 0.03 Cord IGFI 1.17 (0.31–8.74) 0.76 (0.09–5.33) 0.18 Maternal IGFBP3 25.95 (6.54–52.03) 47.1 (10.71–124.73) 0.001 Cord IGFBP3 10 (7–19.8) 14.95 (6.61–41.24) 0.00 Maternal samples were obtained from 25 ND and 25 T1DM consenting mothers at 36 weeks gestation. Cord blood was obtained after delivery. IGFI and IGFBP3 were measured using ELISA. Maternal and cord samples from the two groups were individually amalgamated to perform a western immunoblot for analysis of IGFBP3. IGFI correlated positively with glycaemic control in early pregnancy Maternal IGFI significantly correlated negatively with length of maternal diabetes (r=–0.62, p=0.01). Neither IGFI nor IGFBP3 correlated with birth weight. On Western blot, there was no difference in IGFBP3 bands between cord ND and T1DM groups. In third trimester T1DM serum there was a significant band at 16 kD which was not present in ND third trimester serum. IGFBP3 is significantly increased in maternal and cord serum in T1DM pregnancies compared to ND controls, which explained by increased proteolysis in maternal serum but not in cord. IGFI is decreased in maternal T1DM serum and correlates with glycaemic control and length of diabetes. These results suggest that the normal growth factor axis in pregnancy is abnormal in T1DM pregnancies, which are at higher risk of macrosomia.